The Effect of Virgin Coconut Oil (VCO) Perineal Wound Healing of Postpartum Women in Pondok Jaya District, Depok - Dahlan, Febry Mutiariami; Nabila Azahra; Shinta Novelia (International Health Sciences Journal, 2025)
Background: According to World Health Organization (WHO) data in 2019, the incidence of perineal rupture in mothers giving birth was 2.5 million cases, whre this figure is expected to reach 6.3 million in 2050. Treating perineal wounds in post partum women has become something, the important thing is by carring out good and correct wound care, you can influence the healing process of wound itself and prevent infection in the perineal wound. Objective: This study aims to determine The Effect Of Virgin Coconut Oil (VCO) Perineal Wound Healing Of Postpartum Women In Pondok Jaya District, Depok. Methodology: Experimental research design with a quasi experimental study design with control group post test only. The sample in this study consisted of 30 postpartum patients with grade II perineal wounds which were divided into 2 groups, 15 mothers in the intervention group and 15 mothers into control groups. The sampling technique uses purposive sampling. The research instrument used was the REEDA score observation sheet. The data was analyzed by the Mann-Whitney test. Research Results: The research results showed that there is an effect of Virgin Coconut Oil on the wound healing of perineal of postpartum women in the Pondok Jaya District, Depok (p-value of 0.000 <0.05). Conclusions: There is an effect of wound healing between the intervention group and the control group. Suggestion: It is hoped that the use of Virgin Coconut Oil can be used as a nonpharmacological therapy to help heal perineal wounds for postpartum mothers who have grade II perineal wounds.